Gastric MALT Lymphoma with Biclonal Gammopathy and Bone Marrow Involvement Mimicking Multiple Myeloma - Cáceres-Perkins, William; Cabanillas, Fernando; San Vicente, Glorivette; Rivera-Franceschini, Carlos; Sobrino-Najul, Elías; Vega-Vázquez, Laura I.; Conde-Sterling, Daniel (Puerto Rico Health Sciences Journal, 2020)
Mucosa-associated lymphoid tissue (MALT) lymphomas are B-cell neoplasms that commonly affect the gastrointestinal (GI) tract, usually the stomach. In most cases, extranodal marginal zone lymphoma (ENMZL) is an indolent disease. Bone marrow involvement is common with MALT lymphoma accompanied by paraproteinemia; such involvement impels disease progression. Here, we present the case of an 82-year-old Hispanic patient with long-standing ENMZL in whom the gastric site responded to antibiotic treatment and Helicobacter pylori eradication, but the disease progressed over the years, with a biclonal gammopathy and bone marrow involvement with marked plasmacytic differentiation. In view of this, we suggest the routine evaluation of paraprotein in patients with ENMZL.